Empowering Health Workers as Breastfeeding Counselors to Prevent Stunting At puskesmas Jelakombo, Jombang Regency - Ririn Probowati; Monika Sawitri; Mamik Ratnawati; Heri Wibowo (Community Development Journal, 2022)
The purpose of the activity is to increase knowledge and skills for health workers as breastfeeding counsellors at the Jelakombo Health Center,  Jombang Regency. Training method: lectures, discussions and field practices to counsellors for 5 days with 19 participants consisting of counsellors working at PUSKESMAS PONED. The material provided: the principles of correct breastfeeding, the principle of being a counsellor, the problems faced and how to overcome them in breastfeeding, demonstrations and demonstrations as a counsellor and the direct practice of facing mothers in the community as counsellors.  training methods with the active participation of participants that will result in a faster learning process: presentations, group work and clinical practice The results of the training improve the knowledge, attitudes and behaviour of counsellors in providing education to pregnant and lactating women. Training with methods that involve active participants will make it easier for participants to achieve their goals as counsellors who practice directly with pregnant and lactating women. The results of the program  evaluation found that there was  an increase in knowledge by 47.6% and skills by  57.9%